(untitled) (Jurnal Riset Mahasiswa, 2024)
In the midst of an increasingly rapid world change, The Directorate General of Taxes (DGT) is required to be able to keep abreast of developments and always try to be one step ahead, both in terms of service quality and technological developments in order to provide more effective and efficient services to the public in carrying out their duties collect optimal state revenue. This study attempts to analyze the correlation between motivation, satisfaction, productivity and the Technology Acceptance Model (TAM) at KPP Pratama Yogyakarta by analyzing and testing the relationship between satisfaction and productivity variables with a focus on motivation mediated by TAM. The results of the study show that motivation has a positive effect on job satisfaction and TAM. TAM has a positive effect on job satisfaction and productivity. However, motivation does not have a direct effect on employee productivity at KPP Pratama Yogyakarta.